Empirical Analysis on China IPO Underpricing Phenomenon Based on Investor Sentiment and Issuing System Reforms - Wang, Fei (2013)
This study investigates the causes of the abnormal high initial returns of 963 companies making an initial public offering (IPO) of A-shares during 2006 and 2011 on Shanghai and Shenzhen stock exchanges in China. To find whether the high initial return of IPO shares comes from primary market or secondary market, the research employs stochastic frontier approach to test the existing of underprice of IPO shares in primary market and the analysis result shows that there is no average deliberately underpricing in primary market. The research then turns to investigate the secondary market. Given the immaturity of China stock market and its special institutional environment, the research divides the total 963 data into three sample set based on the periods when issuing reforms are implemented and adopts three regression analyses to investigate the influential factors related to investor sentiment in secondary market and to compare the influencing changes of those factors during the three reform periods. The regression results show that investors’ emotional biases largely affect the level of average IPO underpricing during 2006 and 2011 though the influencing level of investor sentiment is slightly decreasing during the periods. Meanwhile, the degree of average underpricing is largely reduced by marketization reforms in 2009 and 2011, albeit it still remains the highest in the world. Furthermore, by explore the market-oriented reforms in stock market and comparing the empirical results in reform stages, the research infers that the rooted-cause of abnormal high initial return of IPO shares in China is resulted from the long run imbalance of supply and demand in terms of IPO shares.